Managerial Ideology and the Social Control of Deviance in Organizationsby WeissRichard M. New York: Praeger, 1986, 269 pages, $32.85, cloth. - Graham, Jill W. (Academy of Management Review, 1988)
The article presents a review of the book “Managerial Ideology and the Social Control of Deviance in Organizations,” by Richard M. Weiss.